2022
DOI: 10.3389/fnagi.2022.974690
|View full text |Cite
|
Sign up to set email alerts
|

Forsythoside B ameliorates diabetic cognitive dysfunction by inhibiting hippocampal neuroinflammation and reducing synaptic dysfunction in ovariectomized mice

Abstract: BackgroundDiabetes-associated cognitive impairment (DACI) is a common complication of diabetes, and studies have shown that DACI is more severe in postmenopausal patients with diabetes. Forsythoside B (FTS⋅B) can inhibit inflammation and reduce synaptic dysfunction, which can improve cognitive function. However, it has not been confirmed whether FTS⋅B has a reversing or retarding effect on postmenopausal diabetic encephalopathy.MethodsSeven days after bilateral ovariectomy (OVX) or sham surgery, adult female C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Male mouse at the age of 4–5 months were treated with daily cisplatin (3.5 mg/kg/day) through intraperitoneal injection. Notably, previous studies have reported that cisplatin penetrates the blood-brain barrier and persists long-term for about 2–5 weeks after its administration and this dose causes significant neurotoxicity to hippocampal neurons, leading to cognitive impairment in rodents [ 24 ]. The overall experimental procedure is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Male mouse at the age of 4–5 months were treated with daily cisplatin (3.5 mg/kg/day) through intraperitoneal injection. Notably, previous studies have reported that cisplatin penetrates the blood-brain barrier and persists long-term for about 2–5 weeks after its administration and this dose causes significant neurotoxicity to hippocampal neurons, leading to cognitive impairment in rodents [ 24 ]. The overall experimental procedure is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, ten different conformations were studied for a single compound. For each ligand, the ten best docking simulations were obtained against the target molecule [ 52 ]. The results were visualized using the Discovery Studio Visualizer.…”
Section: Methodsmentioning
confidence: 99%